Seasonal Variations of Avifauna of Shallabug Wetland, Kashmir - Dar, Imran A; Dar, Mithas A (Journal of Wetlands Ecology, 2009)
The main thrust in this research work has been given on the evaluation of current status of Avifauna associated with Shallabug wetland. The main objectives were to evaluate the bird population fluctuation, to determine various threats to waterbirds and their habitats, and to present the remedial measures based on the key issues identified. For the purpose of present investigation, the study area was divided systematically into three study units of 700 m² each. Visual census method was used for the estimation of bird population. Visual counting was made with the help of high power field binocular (SG- 9.2) from respective vantage points. The birds were observed on the monthly basis in 2008 and the fluctuation in bird population was determined in different seasons: summer, autumn and winter. The observations were made from 5:00 am to 7:00 am (when they come out from their resting place) and 6:00 pm to 7:00 pm (when they approach towards their resting place). The analysis of the results showed that the Shallabug Wetland is particularly important for migratory bird species and marsh land breeding species. The wetland was also found important for long distance migrants as a stopper site for feeding and resting. The bird population showed fluctuation with site differences as well as with changing seasons. Key words: Wetland, Shallabug, Avifauna, Fluctuation, Wetland management DOI: 10.3126/jowe.v2i1.1853 Journal of Wetlands Ecology, (2009) vol. 2, pp 20-34